Importance of coordination skills essential psychophysical demonstrated competencies as a military specialists - V.O. Lisowski; І.Yu. Mihuta (Physical Education of Students)
The aim - to identify the role and importance of coordination abilities in the manifestation of professionally important qualities of psychophysical military experts. It is established that the exercise of general, special and specific coordination abilities provides the most efficient and reliable psychophysical military readiness and suitability to the successful solution of the tasks of combat mission. It is noted that a professionally-applied physical training future military specialist should focus on the development of a certain amount of knowledge and skills. Also - on the formation of professionally important psychophysical qualities that ensure a high degree of readiness of the military to successfully complete the tasks in extreme conditions. Set of system- level structural relationships of mental and physical indicators of the motor and functional fitness, mental processes, and psychomotor ability to control motor actions in different conditions of military occupation.